Evaluation of the efficacy of papaya seed-based natural adsorbent for synthetic textile wastewater treatment - Bhattacharya Debleena; Lodariya Mital; Addis Ermias; Arunachalam Kantha D.; Mayani Suranjana V.; Nikam Rahul J. (E3S Web of Conferences)
This study explored the application of papaya seed-based activated carbon for removing methylene blue dye from synthetic textile effluent. Batch experiments are used in the study to investigate the adsorption potential of activated carbon. The results demonstrate that papaya seeds derived from activated carbon have the greatest potential for methylene blue adsorption, with an average removal effectiveness of 89.4%. The effects of several parameters such as pH, contact time, adsorbent dose, adsorbent-adsorbate temperature, and starting dye amount or concentration were examined to optimize the adsorption conditions. Maximum dye removal was achieved after 60 minutes of contact time at pH 6.5. The carbon dosage and pH of the solution were discovered to have the greatest influence on the adsorption process. Based on the experimental data, the Langmuir and Freundlich models were identified as the most appropriate fits for the adsorption investigation. In conclusion, activated carbon derived from papaya seeds is a viable and natural bio-adsorbent for removing methylene blue from synthetic textile wastewater.